Photoinitiation of polymerization of Acrylamide by Titanium Dioxide Aqueous Suspension System (مجلة ديالى للبحوث الانسانية, 2022)
The acrylamide monomer is photopolymerized by aqueous Suspension of TiO2 semiconductor (Anatase) at room temperature and light intensity (medium pressure mercury lamp.) of 19.44 mW/cm2. Several parameters were explored that affected the photopolyerization process in this system, and these are:-